Searching the Correct and Appropriate Deterrence Function General Formula for Calculating Gravity Trip Distribution Model - Hitapriya Suprayitno (Institut Teknologi Sepuluh Nopember, 2018)
Trip Distribution Model is a very important part of Transport Modeling. This is a result of a mathematical operation among Trip Generation, Generalized Cost Matrix, and Deterrence Function. Thus, it can be understood easily that having a correct and appropriate Deterrence Function Formula is important. Here, correct means that the curve form is in concordance with typical Trip Length Distribution pattern. While, appropriate means that the function is easy to be manipulated in getting a good conformity with the Trip Length Distribution. Three Deterrence Function types, i.e. negative power, negative exponential, and Tanner, were investigated. The investigation was done upon Negative Power Function, Negative Exponential Function and 4 combinations of Tanner Function. The research result indicates that the Negative Power and the Negative Exponential are correct. While, among the four Tanner Function combinations, the correct ones are only the Tanner Function – Negative Power Negative Exponential and the Tanner Function – Positive Power Negative Exponential. The correct and appropriate Deterrence Functions are the above four Basic Functions multiply by a Constant.